2016
DOI: 10.1002/jor.23496
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinatus tendon overuse results in degenerative changes to tendon insertion region and adjacent humeral cartilage in a rat model

Abstract: The etiology of rotator cuff tendon overuse injuries is still not well understood. Furthermore, how this overuse injury impacts other components of the glenohumeral joint, including nearby articular cartilage, is also unclear. Therefore, this study sought to better understand the time course of tendon protease activity in a rat model of supraspinatus overuse, as well as determine effects of 10 weeks of overuse on humeral head articular cartilage. For these studies, multiplex gelatin zymography was used to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…For muscle, we have previously shown significant fibrous tissue infiltration (indicative of muscle degeneration) 3 weeks following tendon injury . In our previous studies with tendon overuse injuries, we have observed concomitant humeral head cartilage damage by 12 weeks after tendon injury onset.…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…For muscle, we have previously shown significant fibrous tissue infiltration (indicative of muscle degeneration) 3 weeks following tendon injury . In our previous studies with tendon overuse injuries, we have observed concomitant humeral head cartilage damage by 12 weeks after tendon injury onset.…”
Section: Methodsmentioning
confidence: 83%
“…In particular, prior work has identified a positive correlation between amount of cathepsin K present and osteoarthritis severity in mice and cathepsin L has been shown to be upregulated in instances of muscle atrophy in both rats and mice . Additionally, our previous work investigating tendinopathy has demonstrated upregulated cathepsin activity in the tendon at 4 and 8 weeks of overuse in a rat model.…”
Section: Experimental Design and Outcome Measures Performed In All Thmentioning
confidence: 85%
See 2 more Smart Citations
“…[26][27][28] This constriction led to degenerative changes in the tendon, evidenced by increased cellularity, rounder cell shape, and decreased collagen organization. 16,28 Subsequently, another model of overuse tendinopathy was developed using downhill treadmill running, which caused similar degenerative changes; this method can be applied either on its own [29][30][31] or in combination with an artificial subacromial impingement. 26,28 Treadmill running is noninvasive, reproducible, and mimics the local mechanical conditions of supraspinatus impingement in humans, with decreases in tendon properties.…”
Section: Chronic/overuse Models Of Tendon Degenerationmentioning
confidence: 99%